A Composite Forecasting Methodology for Manpower Planning Utilizing Objective and Subjective Criteria - Drandell, Milton (Academy of Management Journal, 1975)
An approach to manpower planning is developed using objective analysis of the past and subjective analysis of the future. The techniques of exponential smoothing and regression analysis provide the final forecast utilizing a computer time sharing network. The importance of management support for the program is discussed.